Planning a One Health Case Study to Evaluate Methicillin Resistant Staphylococcus aureus and Its Economic Burden in Portugal - Igrejas, Gilberto (2019)
Free PMC Article: https://www.ncbi.nlm.nih.gov/pmc/articles/PMC6292916/